ENVIRONMENTAL RISK FACTORS IN THE HOUSE AND PNEUMONIA IN TODDLERS IN INDONESIA 2007 - Khadijah Azhar (Widyariset, 2012)
Pneumonia constitutes the greatest disease that causing death among children under-five in the world. Risk of death can be decreased, if the illness were identified early, treated appropriately and prevention efforts. The study aimed to determine the influence of in-house environmental risk factor against the prevalence of pneumonia in children. The study used cross-sectional design with descriptive method which consisted of 2.408 samples of 80.329 households from Riskesdas 2007 data. Data were analyzed by univariate and bivariate of Chi-square to get the level of risk by odds ratio, as well as the significance of correlation between dependent and independent variables of the study. The results showed that significant correlation between the type of floor (OR = 1.209; CI 95%) and fuel type (OR = 1.683; CI 95%) with prevalence of pneumonia children under-five. Conclusion of the study is that the floor type and the fuel have significant correlation with the prevalence of pneumonia, while the crowding and the presence of household members whom smoke could be not described its correlation clearly.